A Bibliometric Analysis of Research on Ketamine From 2001 to 2020 - Miao, Huihui; Yu, Kang; Gao, Danyang; Lin, Xiaowan; Cao, Ying; Liu, Xiao; Qiao, Hui; Li, Tianzuo (Frontiers in Molecular Neuroscience, 2022)
Background: Ketamine is an intravenous anesthetic with analgesic effects that has a rapid onset and short duration of action. Many studies have been conducted on the use of ketamine; however, the quantity and quality of such studies have not been reported. Therefore, we aimed to conduct a bibliometric analysis of research on ketamine from 2001 to 2020. Methods: We used the Web of Science database to get publications on ketamine from January 2001 to December 2020. Various bibliographic information was collected, including the number of publications, year of publication, country of origin, journal name, research hotspots, citation count, and author information. Results: A total of 5192 articles were included in the analysis. The United States published the highest number of papers on ketamine and the United States participated in publishing the most papers and disclosure funds. The types of articles in clinical trials were cited more frequently. Most articles on ketamine were published in the journal Anesthesia & Analgesia. Furthermore, the antidepressant effect of ketamine has been a research hotspot for the last 20 years. Conclusion: This study provided a comprehensive analysis of research on ketamine and highlighted the growing interest in ketamine and its antidepressant effects.